The Use Of Viscous Dampers For Retrofitting Of Reinforced Concrete Frames - Nasim Shakouri Mahmoudabadi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
During last earthquakes, often the conventional reinforced concrete (RC) buildings had suffered damages. So in conventional RC buildings, earthquake-induced energy is dissipated in components of the gravity and lateral-load-resisting system. The action of dissipating energy in framing such as beams and joints in a moment-resisting frame produces damage in those components. Repair of such damage after an earthquake is typically expensive and often requires evacuation of the building while repair work on the gravity system is undertaken. In this research, adding viscose damper to new and existing RC frames have investigated. So nonlinear dynamic analysis of the systems has been carried out and its structural behavior has been investigated. Results indicate that, this damper enhances the seismic behavior of RC frames. It causes the energy applied to structure due seismic loading, concentrate on damper while other members stand in elastic zone. It evacuation of the building for repair might not be necessary and the total repair cost will likely be minor compared with the costs associated with repair and business interruption in a conventional building.